Kombinasi Metode SAW dan AHP Sistem Penunjang Keputusan Pemberian Pinjaman Bagi UMKM Anggota Koperasi - Randy Anderias Adu; Agus Budiyantara (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Cooperative loans are financial facilities provided by cooperatives to their members to meet funding needs with predetermined terms and conditions. The process includes submission, assessment and disbursement of funds according to members' needs and abilities. This loan generally has a certain interest and repayment period. The aim of the research is to determine the provision of loans in a decision support system using a combination of AHP and SAW methods. The AHP method is an analytical technique for selecting the best alternative in complex decision making, by weighing preferences and criteria, while SAW is a calculation approach that takes into account relative weights for evaluating alternatives in a decision support system. The final result of combining the AHP and SAW methods is to obtain a ranking of the names of cooperative members who are entitled to receive loans, ranging from the best 10 people out of 50 people in each region in Jakarta.